Tramadol use and incident dementia in older adults with musculoskeletal pain: a population-based retrospective cohort study - Si Nae Oh; Hye Jun Kim; Jae Yong Shim; Kyuwoong Kim; Seogsong Jeong; Sun Jae Park; Sang Hyun Lee; Joong Won Ha; Sang Min Park (Scientific Reports)
Abstract We aimed to assess the association of tramadol use with the risk of dementia. This population-based retrospective cohort study using the Korean National Health Insurance Service database included a total of 1,865,827 older adult patients aged 60 years or older with common musculoskeletal pain between January 1, 2003, and December 31, 2007. Individuals who were newly dispensed tramadol (N = 41,963) were identified and propensity score–matched with those who were not (N = 41,963). Over a maximum of 14-year follow-up, the incidence rates (events per 1000 person-years) of all-cause dementia were 6.1 for nonusers, 6.2 for those with cumulative tramadol use of 1–14 days, 7.7 for those with 15–90 days of use, and 8.0 for those with > 90 days of use. Longer cumulative duration of tramadol use was associated with an increased risk of all-cause dementia compared with nonuse (1 to 14 days: aHR 1.06, 95% CI 0.96–1.17; 15 to 90 days: aHR 1.14, 95% CI 1.10–1.35; and more than 90 days: aHR 1.18, 95% CI 1.00–1.39; test for trend: P < 0.001). The results showed a similar pattern for Alzheimer’s disease and were robust across subgroup and sensitivity analyses, but not for vascular dementia. This study found that exposure to tramadol was associated with an increased risk of dementia. Taking this potential risk into consideration, clinicians should carefully weigh potential benefits and risks when prescribing tramadol to older adults with musculoskeletal pain.